Editorial Commentary: All-Inside Anterior Cruciate Ligament Reconstruction: In Pursuit of Ideal Graft Fixation. - Geeslin, Andrew G (Arthroscopy: The Journal of Arthroscopy & Related Surgery, 2019)
With evolution of techniques in orthopaedic surgery, incremental improvements can be anticipated. All-inside anterior cruciate ligament (ACL) reconstruction represents a revolution in treatment of ACL injuries, and further technical modifications may result in gradual improvements. This process of continual optimization of our techniques is important for providing the best possible surgical outcomes. Supplemental fixation of the inner graft limbs may lead to improved time-zero biomechanical performance when all-inside ACL reconstruction is performed. However, in ACL surgery, optimal graft selection and fixation are still debated.